REVITALISASI TATA RIAS TRADISIONAL MINANGKABAU SEBAGAI MEDIA PEMBELAJARAN KOLABORATIF DI ERA DIGITAL - Gifa Ashfani; Saira; Nadya Hanifah; Dwi Anjani; Cantika Kinara Aqila; Ririn Amaliah Putri Sarah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of revitalizing traditional Minangkabau makeup as a collaborative learning medium in the digital era among Grade XI Beauty Department students at SMK Negeri 7 Padang. The research background stems from the low level of students’ mastery of traditional makeup techniques and the limited use of digital media in vocational learning. To address these issues, a collaborative learning model was developed that integrates Minangkabau local wisdom with digital technology through group projects, video-based work documentation, and e-portfolios. This study employed a quasi-experimental method with a one-group pretest–posttest design involving 53 students. Data were collected through makeup skill tests, digital literacy questionnaires, and observations of collaborative learning activities. Data analysis using a paired sample t-test revealed a significant improvement (p = 0.000 < 0.05) between pretest and posttest results. The average increase in skills was 16.3 points, covering mastery of makeup techniques, creativity, collaboration, and digital literacy. Meanwhile, students’ digital literacy improved by an average of 22.4% across the aspects of learning application use, online collaboration, and digital ethics. The results indicate that the implementation of digital-based collaborative learning oriented toward local culture is effective in enhancing students’ vocational competence, digital literacy, and cultural awareness. This learning model also strengthens students’ sense of cooperation, communication, and appreciation of Minangkabau culture. Therefore, the revitalization of traditional Minangkabau makeup serves as a strategic innovation in vocational education that aligns with the Merdeka Belajar(Freedom to Learn) movement in the era of digital transformation.